PENGGABUNGAN GUGATAN PEMBATALAN MEREK DAN GUGATAN ATAS PELANGGARAN MEREK - Elisabeth D.A.N,; R. Rahaditya, (The Juris, 2024)
Problems in registering a mark that is conceptually identical to another mark can be resolved by filing a trademark cancellation lawsuit. However, in drafting a lawsuit, the owner or its attorney must prepare the lawsuit correctly and straight to the issue. Cause lawsuits are often found whose contents are inappropriate, causing the lawsuit become vague and unclear. Thus, in the dispute between Buttonscarves and Umamascarves trademarks, the plaintiff was suing for cancellation of the trademark but asked for a stop to production, sales, and promotion of products from the trademark that were conceptually identical to its own; this claim can only be requested for a trademark infringement lawsuit. This research aims to analyze the combination of trademark cancellation lawsuits and trademark infringement lawsuits. This type of research is normative legal research accomplished with literature studies supported by primary and secondary data obtained from interviews and related legal materials. This research shows that mixing a lawsuit for trademark cancellation and a lawsuit for trademark infringement cannot be fulfilled because different parties are drawn as defendants. In a trademark cancellation lawsuit, the defendant is the registered trademark owner, whereas in a trademark infringement lawsuit, the defendant is the party who does not have the right or permission to use the trademark. Other than that, there are different demands in those lawsuits. In the trademark cancellation lawsuit, the demand is for the trademark cancellation, whereas in the trademark infringement lawsuit, the demand is for compensation or closure of activities related to the trademark.